1991
DOI: 10.1093/jnci/83.11.775
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Cell Invasion Inhibited by TIMP-2

Abstract: The 72-kd type IV collagenase is a member of the collagenase enzyme family that has been closely linked with the invasive phenotype of cancer cells. Previous studies have shown that both normal cells and highly invasive tumor cells produce the 72-kd type IV procollagenase enzyme in a complexed form consisting of the proenzyme and a novel tissue inhibitor of metalloproteinases, TIMP-2. The balance between activated enzyme and available inhibitor is thought to be a critical determinant of the matrix proteolysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
116
2

Year Published

1996
1996
2003
2003

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 291 publications
(127 citation statements)
references
References 0 publications
9
116
2
Order By: Relevance
“…1). Similar anti-invasive properties have previously been reported with other hydroxamic acid based MMPIs [35][36][37] and TIMPs [38][39][40], as well as with anti-gelatinases anti-bodies [39,41]. Because a reduced invasiveness could result from a cytotoxic effect of the inhibitor, cellular viability and metabolism were measured by the WST-1 assay after 48 h of treatment.…”
Section: Anti-invasive Activity Of Gi129471 On Ht1080 Cellssupporting
confidence: 62%
“…1). Similar anti-invasive properties have previously been reported with other hydroxamic acid based MMPIs [35][36][37] and TIMPs [38][39][40], as well as with anti-gelatinases anti-bodies [39,41]. Because a reduced invasiveness could result from a cytotoxic effect of the inhibitor, cellular viability and metabolism were measured by the WST-1 assay after 48 h of treatment.…”
Section: Anti-invasive Activity Of Gi129471 On Ht1080 Cellssupporting
confidence: 62%
“…20 It was long been believed that TIMPs suppressed tumor invasion by inhibiting MMPs in experimental and clinical studies. Recombinant TIMP-2 inhibited the invasion of HT-1080 fibrosarcoma cells in vitro 21 ; and increased TIMPs expression has been correlated with decreased tumor growth, invasiveness, and metastasis in tumor cell lines of the stomach, 22 pancreas, 23 and lung. 24 However, the current study demonstrated that TIMP-2 immunoreactivity was correlated positively with the degree of malignant behavior in thymomas, contrary to previous evidence.…”
Section: Discussionmentioning
confidence: 96%
“…The levels of MMP-2 and MMP-9 in high-grade or invasive bladder cancers were found to be significantly higher than those in low-grade and non-invasive bladder cancers, indicating that MMP-2 and MMP-9 may play a role in the invasion and metastasis of bladder cancer (Davies et al, 1993). TIMPs are known for their anti-neoplastic activity (Albini et al, 1991;Montgomery et al, 1994). The transfection of sense TIMP-I complementary DNA into metastatic cells decreased their invasive, tumorigenic and metastatic capacities (DeClerck et al, 1992;Khokha et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the imbalance of these enzymes and inhibitors is most likely an important factor in urothelial cancer invasion and metastasis, and, thereby, recurrence. There have been several studies on the inhibition of tumour invasion and metastasis by TIMP-1 (Schultz et al, 1988;Alvarez et al, 1990) and TIMP-2 (Albini et al, 1991;DeClerck et al, 1991). Koop et al (1994) found that the decreased metastatic ability of TIMP-overexpressing B 16F10 melanoma cells was due to the effects of TIMP on tumour growth after tumour cell extravasation in the metastatic target organ.…”
Section: Discussionmentioning
confidence: 99%